2007
DOI: 10.1007/bf03194652
|View full text |Cite
|
Sign up to set email alerts
|

The selection of mosaic (MSC) phenotype after passage of cucumber (Cucumis sativus L.) through cell culture — a method to obtain plant mitochondrial mutants

Abstract: Mosaic (MSC) mutants of cucumber (Cucumis sativus L.) appear after passage through cell cultures. The MSC phenotype shows paternal transmission and is associated with mitochondrial DNA rearrangements. This review describes the origins and phenotypes of independently produced MSC mutants of cucumber, including current knowledge on their mitochondrial DNA rearrangements, and similarities of MSC with other plant mitochondrial mutants. Finally we propose that passage of cucumber through cell culture can be used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…Several bases for somaclonal variation have been proposed, which include changes in chromosome number (Mujib et al 2007; Leva et al 2012), point mutations (D’Amato 1985; Ngezahayo et al 2007), somatic crossing over and sister chromatid exchange (Duncan 1997; Bairu et al 2011), chromosome breakage and rearrangement (Czene and Harms-Ringdahl 1995; Alvarez et al 2010), somatic gene rearrangement, DNA amplification (Karp 1995; Tiwari et al 2013), changes in organelle DNA (Cassells and Curry 2001; Bartoszewski et al 2007), DNA methylation (Guo et al 2007; Linacero et al 2011), epigenetic variation (Kaeppler et al 2000; Guo et al 2006; Smulders and de Klerk 2011), histone modifications and RNA interference (Miguel and Marum 2011), segregation of pre-existing chimeral tissue (Brar and Jain 1998; Vázquez 2001; Ravindra et al 2012; Nwauzoma and Jaja 2013) and insertion or excision of transposable elements (Gupta 1998; Sato et al 2011b). In particular, transposable elements are one of the causes of genetic rearrangements in in vitro culture (Hirochika et al 1996; Sato et al 2011a).…”
Section: Molecular Basis Of Somaclonal Variationmentioning
confidence: 99%
“…Several bases for somaclonal variation have been proposed, which include changes in chromosome number (Mujib et al 2007; Leva et al 2012), point mutations (D’Amato 1985; Ngezahayo et al 2007), somatic crossing over and sister chromatid exchange (Duncan 1997; Bairu et al 2011), chromosome breakage and rearrangement (Czene and Harms-Ringdahl 1995; Alvarez et al 2010), somatic gene rearrangement, DNA amplification (Karp 1995; Tiwari et al 2013), changes in organelle DNA (Cassells and Curry 2001; Bartoszewski et al 2007), DNA methylation (Guo et al 2007; Linacero et al 2011), epigenetic variation (Kaeppler et al 2000; Guo et al 2006; Smulders and de Klerk 2011), histone modifications and RNA interference (Miguel and Marum 2011), segregation of pre-existing chimeral tissue (Brar and Jain 1998; Vázquez 2001; Ravindra et al 2012; Nwauzoma and Jaja 2013) and insertion or excision of transposable elements (Gupta 1998; Sato et al 2011b). In particular, transposable elements are one of the causes of genetic rearrangements in in vitro culture (Hirochika et al 1996; Sato et al 2011a).…”
Section: Molecular Basis Of Somaclonal Variationmentioning
confidence: 99%
“…Indeed, mitochondrial mutants exhibiting respiratory impairments have occurred as a result of deletions accompanied by losses of mitochondrial genes, through homologous recombination at short repeat sequences. Examples include the maize nonchromosomal stripes mutant, the cucumber mosaic mutant, tobacco CMS I and CMS II, and the Arabidopsis maternally distorted leaves mutant [48][49][50][51]. In order to preserve mitochondrial functioning there must be a mechanism to suppress free recombination and/or the amplification of irregularly recombined DNA molecules.…”
Section: How Has the Angiosperm Mitochondrialmentioning
confidence: 99%
“…Although the genes responsible have not been identified, plant lines that generate multiple mitochondrial genotypes in their offspring are known. These include maize P2 and cucumber line B [49,57].…”
Section: How Has the Angiosperm Mitochondrialmentioning
confidence: 99%
“…MSC lines were characterized by slower growth, chlorotic mosaic on the leaves and fruit, lower fertility and smaller seed size, affecting plant performance [124,125]. The studies of mtDNA revealed that MSC lines possess complex mitochondrial DNA rearrangements [117,126].…”
Section: Mitochondriomics and Retrograde Signalingmentioning
confidence: 99%
“…It has been proposed that the passage through cell cultures may be used as a way to produce cucumber mitochondrial mutants and to develop efficient mtDNA transformation protocol [120,125]. Cell culture regeneration method that allows to produce lines with affected mitochondrial genome and its expression is a good way to develop cucumber mitochondrial omics.…”
Section: Mitochondriomics and Retrograde Signalingmentioning
confidence: 99%